Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/atmos10100626
|View full text |Cite
|
Sign up to set email alerts
|

Review of PM Oxidative Potential Measured with Acellular Assays in Urban and Rural Sites across Italy

Abstract: This work is an overview of the oxidative potential (OP) values up to date measured in Italy, with the aim to provide a picture of the spatial and seasonal variability of OP in the various geographical areas across Italy. The summarized works used the common acellular assays-based dithiothreitol (OP DTT ), ascorbic acid (OP AA ), glutathione (OP GSH ), and 2 ,7 -dichlorodfluorescein (OP DCFH ) assays. The paper describes the association of OP responses with PM chemical composition, the sensitivity of various a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 52 publications
24
51
0
Order By: Relevance
“…On the contrary, the measured OP AA responses, both volume-and mass-related values, do not show any significant difference between the two sites (Tables S1-S3). This is consistent with several literature papers reporting that the AA assay reactivity is less dependent on PM mass concentration as well as on chemical composition than the DTT response (Bates et al 2019;Calas et al 2018;Fang et al 2016;Hedayat et al 2014;Janssen et al 2015;Perrone et al 2019;Pietrogrande et al 2019a;Visentin et al 2016).…”
Section: Comparison Between Urban and Rural Pm Samplessupporting
confidence: 93%
See 2 more Smart Citations
“…On the contrary, the measured OP AA responses, both volume-and mass-related values, do not show any significant difference between the two sites (Tables S1-S3). This is consistent with several literature papers reporting that the AA assay reactivity is less dependent on PM mass concentration as well as on chemical composition than the DTT response (Bates et al 2019;Calas et al 2018;Fang et al 2016;Hedayat et al 2014;Janssen et al 2015;Perrone et al 2019;Pietrogrande et al 2019a;Visentin et al 2016).…”
Section: Comparison Between Urban and Rural Pm Samplessupporting
confidence: 93%
“…Aqueous solution extraction Water-based extractions were performed for 15 min in an ultrasonic bath using 10 mL of phosphate buffer or Gamble's solution, following the procedure previously used by Authors that has been found to guarantee a good extraction efficiency ≥ 90% (Pietrogrande et al 2019a;Visentin et al 2016). The extracts were then filtered on a regenerate cellulose syringe filter (13 mm, 0.22 μm, Kinesis) to remove the suspended solid particles.…”
Section: Extraction Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies across the Po Valley have shown that PM oxidative potential is influenced by the concentrations of metals (e.g., Cr, Mn, Fe, Ni, Cu) and carbonaceous species (e.g., OC, EC) ( Hakimzadeh et al, 2020 ; Longhin et al, 2020 ; Pietrogrande et al, 2019 ; Visentin et al, 2016 ). These species are mainly associated with road traffic, domestic biomass burning, oil combustion, and SOA across Italy ( Larsen et al, 2012 ; Pietrogrande et al, 2019 ); however, it has been shown that the oxidative potential of PM in the Po Valley region, and in particular in the Milan metropolitan area, is elevated due to the high density of anthropogenic emission sources in conjunction with specific stable atmospheric conditions, favoring the accumulation and aging of particles in the atmosphere ( Perrone et al, 2016 , Perrone et al, 2010 ; Pietrogrande et al, 2019 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The combined application of DPPH and conventional OP assays could then permit, in the future, to gain more knowledge about the reaction and/or competition between oxidative and reducing processes.health impacts than ordinarily used PM mass concentrations [9]. In this context, many acellular assays were developed to measure oxidative potential in order to gain a proxy of this PM capability [10]. There is still no agreement regarding the most representative assay to determine oxidative potential [11], but most commonly used acellular tests include the ascorbic acid (AA) [12] and dithiothreitol (DTT) [13] assays which consist of mimicking the consumption of a physiological and a surrogate antioxidant, respectively, and 2 ,7 -dichlorofluorescin (DCFH) by which particle-bound ROS are determined [14].…”
mentioning
confidence: 99%